Understanding Knowledge Sharing Barriers in Indian Health Care Sector: A Qualitative Inquiry - Venugopalan, Murale; S, Ajay GhoshK; S, Avinash (International Journal of Psychosocial Rehabilitation, 2020)
In todays information world the medical field is undergoing though a series of burgeoning changes. This has led to a situation where diagnosis and treatment interventions are affected by information shared between various members of a medical team comprising of physicians and other health care professionals.This paper investigates how information exchange occurs between various health care professionals and on barriers in sharing knowledge . This paper discusses on two type of knowledge : implicit and explicit in nature. The researchers have adopted a qualitative approach to identify knowledge enablers and barriers in health care setting. The study helped in identifying that communication and trust were essential in facilitating teamwork across diverse organizations (or entities).Further it add that . Miscommunication may lead to misunderstandings affecting task management, workflow, and, eventually, care of patients. Two ways of solving the communication barrier are by turning implicit knowledge into explicit knowledge and by organizing seminars to various parties on the topic.